Engineering characteristics of rocks in Qatar; - Kassem, Ahmed Fawzy (AUC Knowledge Fountain, 2017)

(untitled)
Excavation as well as tunneling have become fundamental operations in the advanced civil engineering field. In Qatar, many subsurface construction operations take place in rocks. However, the lack of studies and research that analyze the subsurface rock components from a geotechnical engineering perspective has created unexpected construction conditions. Most of similar studies handled concerns about properties related to oil and gas fields. This research aims to provide a geotechnical study for rocks in Qatar, and to illustrate the impact of the existence of these rock layers on two civil applications; namely excavation and tunneling. During this study, soil investigation reports and rock samples are collected from several bores located in Qatar, and a classification system is utilized to classify the rock samples to identify and study the properties of the existed rocks. Also, numerous production rates from different tunneling and excavation projects are recorded and analyzed, in order to clarify the relation between these rates and the classified rock layers. Based on this analysis, a geotechnical study and mapping system for the rocks in Qatar are presented. Reliable tools for predicting the average productivities of excavation and tunneling projects in Qatar are developed, these tools are aiming to facilitate designing, bidding and executing processes involved with these types of rocks.